Performance of Fresh Water Fish Contract Farming in Malaysia: Innovative Supply Chain Integration Outlook - Zainol, Mohd Azwan; Abas, Zakaria; Ariffin, Ahmad Shabudin (ExcelingTech, 2019)
This paper conceptualizes the innovative supply chain integration and business performance of aquaculture contract farming setting in Malaysia. Based on the SCM philosophy, it highlights three related variables of supply chain integration, namely: external integration with suppliers, external integration with customers and supply chain risks, and technological innovation, and the relation amongst the variables in focus that could produce promising business performance. Hence, ability to conceptualize, observe and give due recognition to the possible relation amongst these variables in question by the prospective aquaculture contract farming participants that could bring about an insightful engagement for the betterment of the aquaculture business performance.